Performance improvement in mobile air conditioning system using Al2O3/PAG nanolubricant - A. A. M., Redhwan; Azmi, W. H.; M. Z., Sharif; R., Mamat; Mahendran, Samykano; G., Najafi (Springer, 2019)
This paper presents the investigation of Al2O3/PAG nanolubricant performance for a compact vehicle mobile air conditioning (MAC) system. The Al2O3/PAG nanolubricant in this study is prepared by using two-step preparation method and stabilized using 4-Step UV–Vis Spectral Absorbency Analysis. An enhancement in the coefficient of performance (COP), reduction in compressor work, and enhancement in the cooling capacity of MAC employing Al2O3/PAG nanolubricant are recorded up to 31%, 26% and 32%, respectively, for 0.010% volume concentration. The current MAC performance is compared with MAC employing SiO2/PAG nanolubricant from previous study. The comparison shows that the Al2O3/PAG nanolubricant has better performance in term of cooling capacity, compressor work, and COP at an average of 6%, 8%, and 33%, respectively. Therefore, the finding from this study suggests Al2O3/PAG nanolubricant with a volume concentration of 0.010% as an optimum and best performance nanolubricant for MAC systems.